(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
The present study is mainly focused on the design and development of an information system for preserving the results of testing to verify the residual knowledge of students of the resource for training specialists in information and communication technologies. The purpose of the study is to provide a scientific justification for the problem of developing professional training of specialists in information and communication technologies in the process of using an information system to save test results to verify students’ residual knowledge and to verify the effectiveness of its implementation in universities. According to the results of the experiment, it can be argued that the introduction of an information system to preserve the results of testing to test students’ residual knowledge in the educational process contributes to the professional training of specialists in information and communication technologies at the universities of Ukraine. The application of development and utilization of contemporary information technologies concentrated on implementing the pedagogical and psychological aims of teaching and education is fundamentally new mediated by modern technical and technological innovations.